REALIZATION FUNCTIONS OF MARKET ECONOMIC IN THE REPUBLIC OF KAZAKHSTAN AS LEGAL STATE - Koszhanov, Айткул Сагатович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
In the article author consider methods of realization functions of market economic in the Republic of Kazakhstan as legal state.